Tinjauan Etika Praktis terhadap Perceraian Kristen - Samuel Elia; Ferry Simanjuntak (Sekolah Tinggi Teologi Real Batam, 2021)
There has been so much discussion about Divorce among Christians with various theological backgrounds, but for the lay congregation, there is still confusion about the attitude of the Church in general. Of course, this has a less than the optimal effect on the spiritual formation of the church. This may happen because of the lack of understanding Christians about how Christian ethical values can be applied in divorce cases. Moreover, it was added with the uncertainty of some church parties in taking their stand. This paper tries to explain in a simple way about Divorce with all its details, causes, and consequences. This paper also discusses why the church needs to take a stand and show it clearly to the congregation to avoid congregational confusion. This research was made using descriptive qualitative research methods through literature studies. Conclusions are generally drawn based on the inductive method. AbstrakSudah begitu banyak pembahasan mengenai Perceraian di kalangan Kristen dengan berbagai latar Teologi, namun bagi kalangan jemaat awam masih terasa adanya kebingungan mengenai sikap Gereja pada umumya. Tentu saja hal ini memberikan pengaruh kurang optimal dalam pembinaan rohani jemaat. Hal ini mungkin terjadi karena begitu minimnya pemahaman orang-orang Kristen mengenai bagaimana nilai-nilai Etika Kristen dapat diterapkan dalam kasus perceraian. Apalagi ditambah dengan kegamangan beberapa pihak gereja dalam mengambil sikap. Tulisan ini mencoba mengulas secara sederhana mengenai Perceraian dengan segala seluk beluknya, penyebab dan akibat yang ditimbulkan. Tulisan ini juga menbahas mengenai mengapa gereja perlu mengambil sikap dan menunjukkannya secara jelas kepada jemaat agar menghindarkan kebingungan jemaat. Penelitian ini dibuat menggunakan metode penelitian kualitatif desktriptif melalui studi literatur. Kesimpulan secara umum diambil berdasarkan metode induktif.